Tax liability side equivalence in experimental posted-offer markets - Rainald Borck; Dirk Engelmann; Wieland Müller; Hans-Theo Normann (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
In theory, the incidence of a tax should be independent of which side of the market it is levied on. This principle of liability side equivalence underlies virtually all theories of tax incidence. Policy discussions, however, tend to place great emphasis on the legal division of tax payments. We use computerized experimental posted-offer markets to test liability side equivalence. We find that market outcomes are essentially the same when the tax is levied on sellers as when it is levied on buyers. Prices in both treatments are slightly above the competitive equilibrium. Thus we cannot reject liability side equivalence.
urn:nbn:de:kobv:11-10047125
Keywords: H22; C99; 330; Tax Liability; Posted Offer Market; Experimental Economics